THE EFFECT OF SERVICE QUALITY TO PATIENT SATISFACTION AT PATIENT REGISTRATION PUSKESMAS PALANG - AGUSTYA, FA IKA (Sekolah Tinggi Ilmu Kesehatan Sapta Bakti, 2023)
Measurement of service quality and patient satisfaction surveys in the registration section need to be carried out as an evaluation of the services provided. This study aims to analyze the effect of the dimensions of service quality (dimensions of reliability, responsiveness, assurance, empathy, and tangible) with patient satisfaction at the Puskesmas Palang. This research uses quantitative research with a cross-sectional approach. The sample in this study was 96 people. The sampling technique uses accidental sampling. Data analysis using multiple linear regression tests. Based on the partial test (t test) the reliability variable has a significant effect on patient satisfaction at the Puskesmas Palang. Responsiveness variable has a significant effect on patient satisfaction. Assurance variable has a significant effect on patient satisfaction. Empathy variable has a significant effect on patient satisfaction. Direct evidence variable (tangible) has a significant effect on patient satisfaction. So it can be concluded, there is an influence of patient satisfaction on service quality.